VIROLA OLEIFERA: A PROMISING ALTERNATIVE TREATMENT FOR FELINE DERMATITIS – A CASE REPORT (Multiplos Acessos, 2024)
Virola oleifera (Schott) A.C. Smith, is commonly used in Brazilian traditional medicine to treat inflammation and heal mucous membranes. Recently, our group has shown the healing capacity of a formulation prepared with its resin through antioxidant mechanisms that contribute to re-epithelialization and reduction of oxidative stress. Other studies conducted by our group with Virola oleifera resin (VO) have also demonstrated an abundance of antioxidant molecules in its chemical composition, as well as various pharmacological activities in several models related to oxidative stress. Therefore, VO holds promise as a natural therapeutic agent for the treatment of wound healing and inflammatory conditions in both veterinary and human fields. Here, we report the case of a 2-year-old Sphynx domestic cat with a three-month history of skin injury on the neck. Our aim was to test the efficacy of VO resin for the treatment of this animal. A cream was prepared from VO (1%) and applied twice a day for 10 days. After 1 week, there was an improvement in tissue coloration and a macroscopic reduction of the lesion, with successful wound healing within 10 days oftreatment. This is the first report demonstrating the excellent healing effect of the antioxidant VO in a domestic animal.
Keywords: antioxidant; Bicuíba; cats; wound